UMA PROSTITUTA E UMA CIDADE: A CRIAÇÃO DE IDENTIDADE E A ABJEÇÃO EM APOCALIPSE 17 E 18 - MOREIRA, CAMILA HORA SILVA DE SOUZA (2017)
This research proposes a reading of chapters 17 and 18 of the Apocalypse of John through the concept of Abject, presented by Julia Kristeva (1982). The aspects of the horror and the monstrous, which characterize the metaphors of John's Apocalypse, reveal the abjection present in the language of the visionary. The abject has permeated contemporary art and is used to identify contexts and social behaviors. The use of this concept in the biblical literature, as proposed, is given in order to verify the identity that John, author of the book Revelation, intends to offer his audience, as a possibility of a new world. The main metaphor is of the woman, the great prostitute and the great city, who gain contours of the horror and the monstrous. Metaphor has this cognitive aspect of language, which evidences a discourse, an identity and an ideology. In this perspective, after realizing that the abject contains the elements used in the language of the visionary, we turn to the Revelation of John 17 and 18, in order to understand the prophet's speech to his audience.